2003
DOI: 10.1021/ac026330e
|View full text |Cite
|
Sign up to set email alerts
|

Hadamard Transform Microchip Electrophoresis Combined with Diode Laser Fluorometry

Abstract: The application of a Hadamard transform technique to microchip electrophoresis is described. The sample is electrokinetically injected into a separation channel and is then detected by diode laser-induced fluorometry. The sample and buffer solutions are introduced into the channel by controlling the high voltages applied to the solutions, according to a code determined by a Hadamard matrix. The S/N ratio of the signal in the electropherogram can be improved by a factor of 5 in comparison with that obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 16 publications
1
38
1
Order By: Relevance
“…Several portable and miniaturized sensors have been developed over the past years to analyze rapidly changing biological systems. Among these biosensors optical-based systems, light scattering (Schafer and Jamieson, 1979;Wilson et al, 2005), absorptionand transmission- (Jindal and Cramer, 2004) or fluorescence spectroscopy Hata et al, 2003;Toma et al, 2011) are predominately used for cell analysis. A detailed review on integrated on-chip optical detection systems can be found at Kuswandi et al (2007).…”
Section: Integrated Sensing Functions For Microfluidic Cell Analysis mentioning
confidence: 99%
See 1 more Smart Citation
“…Several portable and miniaturized sensors have been developed over the past years to analyze rapidly changing biological systems. Among these biosensors optical-based systems, light scattering (Schafer and Jamieson, 1979;Wilson et al, 2005), absorptionand transmission- (Jindal and Cramer, 2004) or fluorescence spectroscopy Hata et al, 2003;Toma et al, 2011) are predominately used for cell analysis. A detailed review on integrated on-chip optical detection systems can be found at Kuswandi et al (2007).…”
Section: Integrated Sensing Functions For Microfluidic Cell Analysis mentioning
confidence: 99%
“…A detailed review on integrated on-chip optical detection systems can be found at Kuswandi et al (2007). Among cell analysis methods, fluorescence spectroscopy is still the most widely used optical technique for on chip cell detection, due to its superior selectivity and sensitivity and the availability of a broad range of optical labels Hata et al, 2003). Recently, a variety of integrated optical oxygen sensors (Schapper et al, 2009) (Stich et al, 2009;Wang and Meier, 2010;Larsen et al, 2011;Feng et al, 2012;Meier and Fischer, 2013) to combine low-cost and easily available imaging equipment with high-resolution imaging for oxygen sensing in microfluidic systems (Figures 3A,B).…”
Section: Integrated Sensing Functions For Microfluidic Cell Analysis mentioning
confidence: 99%
“…The disadvantages of this coding method were the demands on the power level of the laser and that the label had to be bleachable. In a later article, Hata et al [11] used electrokinetic injection of the sample sequence instead of the laser-bleaching method. They showed an improvement of signal-to-noise ratio of a factor 5, while the theoretical increase in signal-to-noise ratio was 8.…”
Section: Free-space Optics: Multiplexed Detectionmentioning
confidence: 99%
“…The excitation beam can be easily focused and illuminate a small region of the separation channel. Furthermore, diversified wavelengths light emitting diodes and laser diodes can be used as miniaturized excitation sources replacing bulk conventional lasers to realize on-line miniaturized detection [12,13]. There are no doubts that the on-line detection mode is preferred to off-line detection mode for realization of integration and high sensitivity of the microdevices.…”
Section: Introductionmentioning
confidence: 99%